2021
DOI: 10.3389/fmicb.2021.680415
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Acetyltransferase CfGcn5 Regulates Growth, Development, and Pathogenicity in the Anthracnose Fungus Colletotrichum fructicola on the Tea-Oil Tree

Abstract: The tea-oil tree (Camellia oleifera Abel.) is a commercial edible-oil tree in China, and anthracnose commonly occurs in its plantations, causing great losses annually. We have previously revealed that CfSnf1 is essential for pathogenicity in Colletotrichum fructicola, the major pathogen of anthracnose on the tea-oil tree. Here, we identified CfGcn5 as the homolog of yeast histone acetyltransferase ScGcn5, which cooperates with ScSnf1 to modify histone H3 in Saccharomyces cerevisiae. Targeted gene deletion reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
1
27
0
Order By: Relevance
“…Anthracnose, a fungal disease caused by Colletotrichum spp., is one of the most pervasive and important diseases of Ca. oleifera and affects tea-oil yield and product quality, threatening the development of the tea-oil industry in China [ 38 , 39 ]. Breeding disease-resistant varieties is often the best way to manage plant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracnose, a fungal disease caused by Colletotrichum spp., is one of the most pervasive and important diseases of Ca. oleifera and affects tea-oil yield and product quality, threatening the development of the tea-oil industry in China [ 38 , 39 ]. Breeding disease-resistant varieties is often the best way to manage plant diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the appressorium formation rate of the Δ Cfvps29 mutant was significantly reduced. In previous studies on C. fructicola , we found that the CfSNF1 , CfGCN5 , CfVPS39 , and CfVAM7 genes were involved in the regulation of appressorium development, and the mutants completely lost their pathogenicity [ 6 , 8 , 9 , 10 ]. CfVps29 may therefore be important for pathogenicity through its regulatory role in appressorium formation.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracnose is the major disease of Ca. oleifera , which causes substantial financial loss ( Zhang et al, 2021 ). While C. fructicola has been identified as the prominent pathogen causing Ca.…”
Section: Discussionmentioning
confidence: 99%
“…For complementation strain, the CfVam7-9F and CfVam7-10R primers were designed, and the complementary fragments that included CfVAM7 gene and promoter sequences were amplified by PCR. The PCR products were purified and then co-transformed into the yeast competent cell XK-125 with pYF11 vector that was linearized using Xho I [containing bleomycin (BLE)-resistant gene and green fluorescence protein (GPF) gene] to form the complementary carrier pYF11: CfVAM7 ( Zhang et al, 2021 ). The yeast cells were cultured on SD-Trp medium for screening, and the primers CfVam7-7F/GFP-R were used for PCR identification of positive clones.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation